1991
DOI: 10.1111/j.1365-2133.1991.tb00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute infectious erythemas in children: a clinico-microbiological study

Abstract: One-hundred children with an acute illness comprising fever and widespread erythematous rash were prospectively studied to determine whether clinical presentations are helpful in defining the causative agent and to identify the most appropriate microbiological specimens. An infectious agent was identified in 65 children; 72% were viruses, 20% were bacteria, 5% were Mycoplasma pneumoniae and in 3% both viruses and bacteria were detected. The most common infectious agents were picornaviruses, an atypical present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 17 publications
2
31
1
3
Order By: Relevance
“…The authors [9] considered the relevance of RV with regard to the rash questionable. We have not been able to find any other cases of association between RV infection and exanthetn in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The authors [9] considered the relevance of RV with regard to the rash questionable. We have not been able to find any other cases of association between RV infection and exanthetn in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 100 children with acute febrile illness and widespread erythematous rash, Goodyear et al [5] identified an infectious agent in 65% children: 72 were viruses, 20% bacteria, 5% Mycoplasma and 14% both viruses and bacteria, while 35% of the children remained undiagnosed. For the patients in our study, laboratory confirmation of a viral or bacterial etiology was even lower.…”
Section: Discussionmentioning
confidence: 99%
“…Age at inception and evolution time were compared by means of the Kruskal-Wallis test (two-tailed with · = 0.05) [4]. Concordance was defined as the coincidence between diagnoses of the consulting pediatric departments and the Pediatric Dermatology Department, and the Î coefficient was used to evaluate it [5].…”
Section: Methodsmentioning
confidence: 99%
“…Goodyear ve arkadaşlarının 1991 yılında 100 ateşli, döküntülü çocuğun tanılarının araştırıldığı çalışmasının sonuçlarında 65 vakada enfeksiyon hastalıkları saptanmıştır. Bunlar içinde %65'ini viral döküntülü hastalıklar, %20'sini de bakteriyel enfeksiyonlar oluşturmuştur (5). Bu araştırma göstermektedir ki ateşli döküntünün görüldüğü hastalarda en sık neden olarak viral enfeksiyonlar öne çıkmaktadır.…”
Section: Introductionunclassified